Implicit Learning in Production: Productive Generalization of New Form-Meaning Connections in the Absence of Awareness - Bovolenta, Giulia; Williams, John N (Wiley, 2023)
AbstractSecond language implicit learning research has shown that a variety of linguistic features can be acquired without awareness. However, this research overwhelmingly uses comprehension tests to measure implicit learning. It remains unclear whether newly acquired implicit knowledge can also be recruited for production. To address this question, we developed a novel paradigm based on elicited recall and false memory that was used to both train participants and test their implicit knowledge in production, including generating new instances of the rule. Participants learned a semiartificial language containing a rule based on one in a natural language (the alternation between Czech spatial prepositionsvandna). Participants who remained unaware of the rule, as assessed by verbal report, nevertheless were able to use it in a production test involving novel items, while believing that they were performing a cued recall test. Even without extensive training, newly acquired implicit knowledge can immediately be evident in production.
Funder: Economic and Social Research Council; Id: http://dx.doi.org/10.13039/501100000269
Keywords: implicit learning; language; production; elicited recall; false memory